2022
DOI: 10.1155/2022/6706622
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture at Zusanli Alleviates Sepsis by Regulating the TLR4-MyD88-NF-Kappa B Pathway and Diversity of Intestinal Flora

Abstract: Background. Electroacupuncture (EA) at the Zusanli acupoint (ST36) has shown therapeutic potential for sepsis due to its ability to limit inflammation and to regulate gastrointestinal tract symptoms. However, the mechanisms contributing to the effects of EA at ST36 on sepsis and connections with the intestinal flora remain unclear. This study was designed to explore the effects of EA at ST36 on Toll-like receptor 4 signaling and the intestinal flora. Methods. ICR mice were randomly divided into 4 groups: contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Degradation of IκB allows the NF-κB complex to reach the nucleus and initiate transcription of genes encoding inflammatory factors [109] . By downregulating the TLR4/MyD88/NF-κB signaling axis, Zhan et al [110] further demonstrated that EA at “Zusanli (ST36)” could reduce the production of inflammatory factors such as IL-1β, IL-6, and TNF-α, consequently inhibiting the inflammatory response and stopping the progression of sepsis. Huang et al [111] identified another upstream molecule STING.…”
Section: Immunological Basis Of Ea To Alleviate Sepsismentioning
confidence: 99%
“…Degradation of IκB allows the NF-κB complex to reach the nucleus and initiate transcription of genes encoding inflammatory factors [109] . By downregulating the TLR4/MyD88/NF-κB signaling axis, Zhan et al [110] further demonstrated that EA at “Zusanli (ST36)” could reduce the production of inflammatory factors such as IL-1β, IL-6, and TNF-α, consequently inhibiting the inflammatory response and stopping the progression of sepsis. Huang et al [111] identified another upstream molecule STING.…”
Section: Immunological Basis Of Ea To Alleviate Sepsismentioning
confidence: 99%
“…Evidence suggests [ 81 ] that electroacupuncture at ST36 can activate the MAPK signaling pathway by modulating gut flora in a model of colitis, affecting ERK1/2 and JNK subfamily signaling molecules, upregulating the expression of intercellular junction complex proteins zona occludens 1 (ZO-1), Occludin, E-Cadherin, Mucin 2 (MUC2), and reduce apoptosis and oxidative stress in intestinal epithelial cells (IECs) to protect intestinal barrier integrity, and reduce disease activity index (DAI) and histological scores in chronic colitis. Studies have found [ 82 , 83 ] that the overall structure of the intestinal flora was adjusted with the improvement of the degree of intestinal inflammation. Electroacupuncture at ST36 modulates and recognizes TLR on the IEC, which are channeled through the TLR4/myeloid differentiation factor 88 (MyD88) signaling pathway to induce activation of immune cell responses, while activation of the TLR4/MyD88 signaling pathway can affect the downstream NF-κB signaling pathway, modulating inflammatory signaling cascades and inhibition of the secretion of pro-inflammatory mediators C-reactive protein (CRP), interferon-γ (IFN-γ), TNF-α, IL-6, and Influence the overall structure of Lactobacillus reuteri, Lactobacillus vaginalis, Bacteroidales, and Firmicutes , and reduce colonic mucosal damage.…”
Section: Effect Of Acupuncture At St36 On Different Systemic Diseasesmentioning
confidence: 99%